Impact of vaccination on the reproductive performance of multiparous Nellore cows - Ferreira, Luiz C.L.; Fernandes, Henrique J.; Silva, Aline G.; Fernandes, Carlos E.; Dutra, Iveraldo S. [UNESP]; Pupin, Rayane C.; Lemos, Ricardo A.A. (FapUNIFESP (SciELO), 2018)
Two experiments were conducted to evaluate the impact of two vaccines on the reproductive performance of multiparous beef cows in Mato Grosso do Sul, Midwest Brazil. In Experiment 1,765 calved multiparous Nellore cows were subjected to the same fixed-time artificial insemination (FTAI) protocol and rebred. Ultrasound pregnancy diagnosis was performed 30 and 90 days post-FTAI (DPI). Rates of pregnancy and pregnancy loss were determined for three periods: from 30 to 90 DPI, from 30 DPI to calving, and from 90 DPI to calving. The cows were assigned to three groups with different vaccination protocols - namely, Group VACMULT (n=250): vaccine against bovine herpesvirus 1 (BoHV-1), bovine viral diarrhea virus (BVDV), and leptospirosis; Group VACL (n=245): vaccine against leptospirosis alone, Group NOVAC (n=270): no vaccination. Serum antibody titers for BoHV-1, BVDV, and leptospirosis, measured in 57 cows from each group indicated active infection, suggesting circulation of these pathogens in the herd. No differences in pregnancy rates were observed across groups. Pregnancy loss rates did not differ significantly across groups within any of the periods investigated (30 to 90 DPI, 30 DPI to calving, or 90 DPI to calving). In Experiment 2, two vaccination protocols for each vaccine were investigated. Group VACGEST was vaccinated on day zero of FTAI (D0) and again 30 days post-FTAI (30 DPI). Group VACPREV was vaccinated on D0 and again on the day of insemination (D11). No significant difference was observed between groups, or significant gestational loss in the group that received the second vaccine on the day of insemination. The results revealed that neither vaccine interfered with the reproductive performance of multiparous cows. No differences were observed between vaccination carried out on both D0 and D11 and that performed on both D0 and D30. The performance of the IBR/BVDV/Leptospirosis vaccine on the day of the artificial insemination did not cause adverse effects on the reproductive parameters.
Keywords: Cattle; Nellore cows; Performance; Reproduction; Reproductive diseases; Vaccination